No association between cortical lesions and leptomeningeal enhancement on 7-Tesla MRI in multiple sclerosis. (February 2020) - Ighani, Mehrnaz; Jonas, Samuel; Izbudak, Izlem; Choi, Seongjin; Lema-Dopico, Alfonso; Hua, Jun; O'Connor, Erin E; Harrison, Daniel M
Background: Autopsy data suggest a causative link between meningeal inflammation and cortical lesions (CLs) in multiple sclerosis (MS). Objective: To use leptomeningeal enhancement (LME) and CLs on 7-Tesla (7T) magnetic resonance imaging (MRI) to investigate associations between meningeal inflammation and cortical pathology. Methods: Forty-one participants with MS underwent 7T MRI of the brain. CLs and foci of LME were quantified. Results: All MS participants had CLs; 27 (65.8%) had >1 focus of LME. Except for hippocampal CL count (ρ = 0.32 with spread/fill-sulcal pattern LME, p = 0.042), no significant correlations were seen between LME and CLs. Mean cortical thickness correlated with the number of LME foci (ρ = –0.43, p = 0.005). Participants with relapsing–remitting multiple sclerosis (RRMS) showed no correlation with neocortical CLs, but significant correlations were seen between LME and hippocampal lesion count (ρ = 0.39, p = 0.030), normalized cortical gray matter (GM) volume (ρ = –0.49, p = 0.005), and mean cortical thickness (ρ = –0.59, p < 0.001). Conclusion: This study supports a relationship between LME and cortical GM atrophy but does not support an association of LME and neocortical CLs. This may indicate that meningeal inflammation is involved with neurodegenerative inflammatory processes, rather than focal lesion development.